Spectroscopic and Electrochemical Studies of Interaction of Cu(II) Ion with Different Aliphatic and Aromatic Amine Based Ligands in Aqueous Solutions: Interaction of Cu(II) Ion with Different Aliphatic and Aromatic Amine Based Ligands (Dhaka University Journal of Science, 2024)
The composition and stability constant of the complexes of copper(II) with the ligands 2,2 –bipyridine, 1,10-phenanthroline, saccharin, and ethylenediamine tetraacetic acid (EDTA),were determined, as well as the effect of temperature on the thermodynamic parameters were studied. The metal-to-ligand ratio in the EDTA complex is found 1:1 and in the rest of the cases, the ratio is 1:2. The redox behavior of the Cu (II) / Cu (0) system in the Cu-ligand complex has been studied in KCl solution as a supporting electrolyte. The redox process of the Cu (II) / Cu (0) system in the Cu-sac complex is almost similar to that of the Cu (II) solution in the absence of any ligand. In other cases, the redox process is a single-step 2-electron transfer process. The electron transfer process in all the cases is diffusion-controlled. The values of peak current ratio and peak potential separation are the evidence that the redox processes are quasi-reversible.Dhaka Univ. J. Sci. 72(2): 61-67, 2024 (July)